Sequestration of soil carbon by burying it deeper within the profile: A theoretical exploration of three possible mechanisms. (December 2021) - Kirschbaum, Miko U.F.; Don, Axel; Beare, Michael H.; Hedley, Mike J.; Pereira, Roberto Calvelo; Curtin, Denis; McNally, Sam R.; Lawrence-Smith, Erin J.
Abstract: Subsoil carbon is generally older and decomposes more slowly than topsoil carbon. It has, therefore, been suggested that carbon stocks could be increased by burying carbon-rich topsoil at depth to slow its decomposition. This has been supported by recent experiments that showed that buried topsoil carbon indeed decomposed more slowly, but the mechanisms causing the reduction have not yet been identified. We investigated three theoretical mechanisms that may explain reduced decomposition rates at depth: (1) lower soil-temperature variability, (2) lower oxygen concentrations/redox potential and (3) less priming (biological synergy). Temperature variability decreases with soil depth. As decomposition rates vary non-linearly with temperature, reduced temperature variability should, therefore, reduce annual decomposition rates. However, detailed simulations showed that it changed annual decomposition rates by only a few percent. Maximal decomposition rates also require adequate oxygen, but our simulations showed that oxygen diffusion rates would need to be reduced 1000 to 10 000-fold compared to the topsoil for it to protect buried soil carbon. Oxygen limitation is, therefore, likely to be confined to soils that are water-logged for extended periods. Priming (or biological synergy) is assumed to be the stimulation of decomposition rates by the availability of labile organic carbon. Our simulations showed that lower labile carbon inputs could reduce priming and potentially preserve up to half of buried carbon for centuries. If experimental work can further substantiate the role of this mechanism, carbon burial at depth could become a practical and useful climate-change mitigation option. Graphical abstract: Image 1 Highlights: We theoretically explored why soil carbon at depth might be more stable. We tested temperature variability, O2 requirements and priming (biological synergy). More even temperatures at depth reduce decomposition rates but by only a few percent. Reduced O2 access by extreme diffusion limits (water-logged) can reduce decomposition. Cessation of biological synergy (priming) can explain persistence of C at depth.